2012
DOI: 10.1097/ftd.0b013e3182557342
|View full text |Cite
|
Sign up to set email alerts
|

Target Concentration Intervention in Oncology

Abstract: Therapeutic drug monitoring (TDM) and more recently target concentration intervention (TCI) have been widely used in clinical practice for the optimization of drug treatment. TDM and TCI have been applied most frequently in the cardiovascular, respiratory, neurology, and infectious disease areas because the medications used here have both narrow therapeutic indices and a clear relationship between concentration and effect. However, apart from drugs such as methotrexate and 5-fluorouracil, the clinical applicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 84 publications
0
14
0
Order By: Relevance
“…Therapeutic drug monitoring (TDM) focuses on the measurement and interpretation of drug serum concentrations in relation to a therapeutic range, but TDM is rarely undertaken. 4 Hence, an alternative strategy, target concentration intervention (TCI) has been proposed 4,5 and a target concentration instead of a range is used. In TCI, a target concentration is selected and pharmacokinetic parameters for the patient are calculated according to the relevant covariates and used to estimate initial dose to achieve the target concentration.…”
Section: What Is Known and Objectivementioning
confidence: 99%
See 1 more Smart Citation
“…Therapeutic drug monitoring (TDM) focuses on the measurement and interpretation of drug serum concentrations in relation to a therapeutic range, but TDM is rarely undertaken. 4 Hence, an alternative strategy, target concentration intervention (TCI) has been proposed 4,5 and a target concentration instead of a range is used. In TCI, a target concentration is selected and pharmacokinetic parameters for the patient are calculated according to the relevant covariates and used to estimate initial dose to achieve the target concentration.…”
Section: What Is Known and Objectivementioning
confidence: 99%
“…6 To perform TCI, one of the prerequisites is building an appropriate population pharmacokinetic model (PopPK). 4,5 During TCI, drug concentration is used to evaluate the clinical effects and to estimate the patient's individual parameters and subsequently to adjust the dosage if the target effect is not reached. 9,10 In TDM of vancomycin in many Chinese hospitals, peak concentration as well as trough concentration is monitored.…”
mentioning
confidence: 99%
“…Clinically, the target concentration intervention (TCI) has been widely applied and can help maximize clinical benefits [23,24] . For TCI, a proper Pop-PK model is required [25,26] and is valuable in highly variable populations that are receiving a drug with a narrow therapeutic window, eg, vancomycin [27] . TCI focuses on the estimation of the initial dose to achieve the target concentration by calculating the pharmacokinetic (PK) and pharmacodynamic (PD) parameters according to the relevant covariates, such as dosage, treatment duration, and clinical effects during treatment [28] .…”
Section: Introductionmentioning
confidence: 99%
“…Higher initial doses are also given, with the aim of achieving early high serum rituximab concentrations and maintaining the concentrations longer , thus providing a higher overall exposure. In a phase II study, higher PFS and overall survival were shown in study participants with poorer prognosis under the SMARTE‐R‐CHOP‐14 in comparison with the schedule used in the RICOVER‐60 trial . Furthermore, pharmacokinetic analysis showed that maximal rituximab trough concentrations were indeed achieved earlier and remained in the serum for a longer time.…”
Section: Factors Affecting Rituximab Exposurementioning
confidence: 99%
“…The existence of such a concentration–effect relationship might potentially serve as the basis for therapeutic drug monitoring and target concentration intervention, i.e. modifying dose according to concentrations and response, for optimizing the use of rituximab in patients with CD20 + lymphoproliferative disorders . Although the literature for rituximab is sparse, there have been studies demonstrating relationships between PK/PD factors of other chemotherapeutic drugs for haematological malignancies with clinical outcomes.…”
Section: Rituximab and Pharmacokinetic–pharmacodynamic Modellingmentioning
confidence: 99%